FRAUD TRIANGLE PADA PEMERINTAH PROVINSI DI INDONESIA - Wulandari, Desi; Oktarida, Anggeraini; Aprianti, Siska (Jurnal Riset Terapan Akuntansi, 2025)
This study was conducted to analyze the effect of pressure, opportunity, and rationalization factors, each of which is measured using the independent variables of regional autonomy, audit opinion, and employee expenditure ratio on fraud in provincial governments in Indonesia. The research data is secondary data derived from the Audit Report (LHP) on the Provincial Government Financial Report (LKPD) and the District Court's decision in 2018-2022. The research population includes 38 provinces in Indonesia with a total unit of analysis (sample) determined as much as 154 data through purposive sampling technique. The data were collected using documentation techniques which were then analyzed through panel data regression using the EViews 12 application. This study found that regional autonomy has a positive effect on fraud. Employee expenditure ratiohas a negative effect on fraud. Meanwhile, audit opinion does not affect fraud. This study provides information that local governments should be able to tighten internal supervision in line with the implementation of regional autonomy and be aware of various actions that can become pressure, opportunities, and rationalizations to commit fraud. Keywords: Fraud, Regional Autonomy, Audit Opinion, Employee Expenditure Ratio